Predictivity of Antemortem Findings on Postmortem Inspection in Italian Heavy Pigs Slaughterhouses - Sergio Ghidini (Animals, 2021)
Pigs slaughtered in European abattoirs must be submitted to antemortem inspection (AMI) and postmortem inspection (PMI), as required by the current European legislation in the matter of official controls. AMI and PMI are equally essential to guarantee food safety and to monitor swine health and welfare. However, little is known about the ability of AMI to predict conditions that are possibly found during PMI. In this study, such a correlation was explored together with the assessment of conditions typically found during AMI and PMI in heavy pigs slaughtered in two Italian slaughterhouses. An assessment scheme containing 13 variables for AMI and 34 lesions for PMI was used for the scope. The herd size was also considered as a variable and included in the study. A total of 24,510 pigs and 30,961 pigs were assessed during AMI and PMI, respectively. The most common conditions found were manure on the body covering more than 30% of the body (dirt >30%) and pluck lesions (‘pleurisy’, ‘pericarditis’, and ‘pneumonia’) for AMI and PMI, respectively. A significant correlation (p < 0.05) between some antemortem (AM) findings and postmortem (PM) conditions was found. In particular, the AM conditions ‘dirt >30%’and ‘skin lesions’ were positively related with PM conditions ‘skin wounds’ and ‘dermatitis’, while the complexes of respiratory and kidney lesions were predicted only by the condition ‘dirt >30%’. The variable ‘standardized herd size’ was negatively associated with ‘milk spot liver’ and positively associated with ‘arthritis/bursitis’. The results of this study show that findings reported during AMI can potentially be used to predict certain conditions found in pigs at PMI. These data can be useful for the competent authorities in characterizing swine farms using a risk-based approach and in developing systems and specific plans for official controls.